A case series of favorable vessel dilatation using a nitinol scoring element–equipped helical balloon catheter (AngioSculpt®). Issue 1 (May 2019) - Sato, Ryo; Sato, Tetsuhiko; Shirasawa, Yuichi; Kondo, Chika; Tadakoshi, Masao; Fukuda, Michio; Ohte, Nobuyuki; Morozumi, Kunio
Objective: Although percutaneous transluminal angioplasty is an effective therapy against vascular access failure in hemodialysis patients, recurrent stenosis imposes enormous burden for hemodialysis patients. A nitinol scoring element–equipped helical balloon catheter (AngioSculpt ® ) has been altered the landscape for treating several vascular diseases. It is not, however, fully elucidated whether AngioSculpt for advanced vascular access stenosis, difficult to expand by conventional balloons, successfully provides bailout angioplasty. Here, we report our cases whose intradialytic venous pressure significantly improved after percutaneous transluminal angioplasty without any serious adverse complications using AngioSculpt. Patients and Methods: Among patients undergoing hemodialysis in Masuko Memorial Hospital, 16 cases with resistant and recurrent vascular access stenosis underwent AngioSculpt (diameter 6 mm, total length 4 cm) angioplasty. We simultaneously measured the average venous pressures during hemodialysis before and after percutaneous transluminal angioplasty. Results: The average outflow vessel stenosis rate was 73.0 ± 11.3% before AngioSculpt intervention. Fully enlarged vessels were observed by expanding vessels at maximum pressure of 14 atm in all cases without any complications including vascular ruptures. Their intradialytic venous pressures decreased from 181.8 ± 39.2 mmHg to 150.5 ± 39.3 mmHg ( p < 0.0001). Conclusion: AngioSculpt may provide a promising option for treating hemodialysis patients with severely advanced vascular access stenosis, who would otherwise need repeated vascular access surgeries and/or conventional percutaneous transluminal angioplasties.